Skeletal Development of Mice Lacking Bone Sialoprotein (BSP) - Impairment of Long Bone Growth and Progressive Establishment of High Trabecular Bone Mass - Bouleftour, Wafa (Public Library of Science, 2014)
Adult Ibsp-knockout mice (BSP−/−) display shorter stature, lower bone turnover and higher trabecular bone mass than wild type, the latter resulting from impaired bone resorption. Unexpectedly, BSP knockout also affects reproductive behavior, as female mice do not construct a proper "nest" for their offsprings. Multiple crossing experiments nonetheless indicated that the shorter stature and lower weight of BSP−/− mice, since birth and throughout life, as well as their shorter femur and tibia bones are independent of the genotype of the mothers, and thus reflect genetic inheritance. In BSP−/− newborns, µCT analysis revealed a delay in membranous primary ossification, with wider cranial sutures, as well as thinner femoral cortical bone and lower tissue mineral density, reflected in lower expression of bone formation markers. However, trabecular bone volume and osteoclast parameters of long bones do not differ between genotypes. Three weeks after birth, osteoclast number and surface drop in the mutants, concomitant with trabecular bone accumulation. The growth plates present a thinner hypertrophic zone in newborns with lower whole bone expression of IGF-1 and higher IHH in 6 days old BSP−/− mice. At 3 weeks the proliferating zone is thinner and the hypertrophic zone thicker in BSP−/− than in BSP+/+ mice of either sex, maybe reflecting a combination of lower chondrocyte proliferation and impaired cartilage resorption. Six days old BSP−/− mice display lower osteoblast marker expression but higher MEPE and higher osteopontin(Opn)/Runx2 ratio. Serum Opn is higher in mutants at day 6 and in adults. Thus, lack of BSP alters long bone growth and membranous/cortical primary bone formation and mineralization. Endochondral development is however normal in mutant mice and the accumulation of trabecular bone observed in adults develops progressively in the weeks following birth. Compensatory high Opn may allow normal endochondral development in BSP−/− mice, while impairing primary mineralization.